2009
DOI: 10.1111/j.1872-034x.2009.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of the extracellular water ratio for assessment of cirrhotic patients with and without ascites

Abstract: Liver cirrhosis was characterized by a redistribution of body water. The ECW ratio is a reliable tool for quantification of redistribution of body water and can predict the development of ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
3
23
0
2
Order By: Relevance
“…In the present study, there were no patients in the uncompensated stage with edema/ascites, therefore body composition was measured with relative accuracy. The device, which is used in this study for measuring body composition, defines an oversaturated state when the extracellular fluid ratio is ≥0.398 . We confirmed that there were no patients beyond a 0.398 extracellular fluid ratio in this study.…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, there were no patients in the uncompensated stage with edema/ascites, therefore body composition was measured with relative accuracy. The device, which is used in this study for measuring body composition, defines an oversaturated state when the extracellular fluid ratio is ≥0.398 . We confirmed that there were no patients beyond a 0.398 extracellular fluid ratio in this study.…”
Section: Discussionsupporting
confidence: 75%
“…According to a study by Hara et al, 24 ECW/TBW ratio proved more reliable for predicting the development of ascites in patients with cirrhosis, a finding which our outcomes seem to corroborate. Even in patients with fluid imbalance, TBW showed no significant change.…”
Section: Discussionsupporting
confidence: 87%
“…There was no difference in the prevalence of sarcopenia in cirrhotic patients with (14/55, 25%) and without ascites (26/106, 25%). We previously reported that a relative expansion of ECW (i.e., more than 0.398) was associated with peripheral edema in patients with cirrhosis (13). Cirrhotic patients with a high ECW ratio (>0.398) had a significantly (p<0.05) higher prevalence of sarcopenia (25/73, 34%) than those with a (18/88, 17%).…”
Section: Relationships Among Cirrhosis Patients' Background Charactermentioning
confidence: 89%